Direction and Problems of Foreign Trade in Nepal - Sharma, Shashikala (Rupantaran: A Multidisciplinary Journal, 2020)
Foreign trade or international trade is the transaction of goods and services between two or more countries. It plays a vital role in developing the economy of a country. The purpose of this study was to identify the direction and problems of foreign trade in Nepal, and to find out the possibilities of foreign trade expansion of the period from fiscal year 2011/12 to 2018/19. The study used quantitative data collected from secondary sources consulting physical library and internet. It was found in the study that most of the foreign trade of Nepal is directed to India. It was also found that there was deficit trade balance as there was decreasing export and increasing imports. As a result, the trade balance is negative and growing every year. Further, the foreign trade in Nepal is highly dependent with India which needs to be diversified to rest of the world.